Validation of an Instrument for Measuring Adherence to Treatment With Immunomodulators in Patients With Multiple Myeloma - Silveira, Lívia Pena; Menezes de Pádua, Cristiane Aparecida; Drummond, Paula Lana de Miranda; Malta, Jéssica Soares; Marques dos Santos, Roberta Márcia; Costa, Naiane Lima; Machado, Taísa Roberta Lopes; Reis, Adriano Max Moreira (Frontiers in Pharmacology, 2021)
Background: Validate the Treatment Adherence Measure (TAM) instrument in outpatients with MM concerning construct validity, reliability and the ceiling and floor effects. Methods: This cross-sectional study included patients diagnosed with MM previously treated with an immunomodulator for at least one month, aged 18 or over, and followed-up in the investigated outpatient clinics. Adherence to immunomodulators was measured by TAM. The TAM’s reliability was assessed using Cronbach’s alpha; The association between adherence and health-related quality of life was investigated to analyze the divergent and convergent construct, measured by the Quality of Life Questionnaire core (QLQ-C30) and the Quality of Life Questionnaire Multiple Myeloma module (QLQ-MY20). The presence of a ceiling or floor effect in the TAM was also analyzed. Results: Eighty-four patients were included in the study, achieving 97.6% adherence. Cronbach’s alpha was 0.41, and the hypothesis of convergent construct validity was confirmed, with statistical significance, in contrast to the hypothesis of divergent construct validity. The presence of the ceiling effect in TAM suggested that this instrument does not allow changes to be detected in individuals concerning adherence to IMiDs. Conclusion: The study concluded that the TAM instrument did not show satisfactory validity and reliability to measure MM’s adherence. MM patients treated at oncohematological outpatient clinics in a metropolitan region of southeastern Brazil showed high adherence to IMiDs.